Short-term health policy responses to crisis and uncertainty - Hornung, Johanna and Bandelow, Nils C. (Journal of Social Policy)
The onset of the economic crisis more than a decade ago posed extreme challenges to health care systems that may now be repeated with the COVID-19 pandemic. The resulting policies produced a wide range of (in some cases, even opposite) outcomes: increased or decreased public expenditures for health care. Curiously, however, countries that were considered particularly hard hit by the economic crisis showed different extremes of policy outcomes. Investigating these developments requires a dynamic view and identifying explanations for government action in one direction or the other. Using the lenses of several theoretical perspectives in public policy research, this article analyses the conditions under which public health expenditures changed in European Union member states after the financial crisis. Why did certain countries, at first sight similarly affected, show opposite outcomes? A Qualitative Comparative Analysis (QCA) confirms that left-wing governments and coordinated market economies, in combination and alone, tended to increase public health expenditures in the short term, whereas countries where neither of these conditions was present decreased public health expenditures.- Reproduced
Keywords: Health policy, European union, QCA, Health expenditure, Crisis